The phytoecdysteroid β-ecdysone is genotoxic in Rodent Bone Marrow Micronuclei and Allium cepa L. Assays - Neves, Camila Siqueira; Gomes, Shaiany Sabrina Lopes; Santos, Tatianne Rosa dos; Almeida, Mariana Macedo de; Souza, Yamara Oliveira de; Garcia, Raúl Marcel González; Otoni, Wagner Campos; Chedier, Luciana Moreira; Viccini, Lyderson Facio; Campos, José Marcello Salabert de (Journal of Ethnopharmacology, 2015)
Ethnaopharmacologial relevance In South America, the β-ecdysone ecdysteroid has been found in species of the genus Pfaffia Mart. Due to the similar morphology of its roots to the Panax ginseng C. A. Mey. (Korean ginseng), some species of this genus has been known as Brazilian ginseng and have been used as tonic and aphrodisiac, as well as for the treatment of diabetes and rheumatism. Here we report a cytogenotoxic evaluation of β-ecdysone (a natural ecdysteroid found in plants) in Rodent Bone Marrow Micronuclei and Allium cepa Assays. Three β-ecdysone (pure) concentrations (based in human therapeutic dosage) were used in the Micronucleus Assay. The animals were treated during two consecutive days. Micronucleated cells were counted in 2000 polychromatic erythrocytes per animal. For A. cepa L. Assay, one β-ecdysone concentration was analyzed. The onions bulbs were exposed for 24 h. The Micronucleus Assay showed genotoxic effects for all treatments, expressed by an increase of micronucleated cells. In A. cepa L. Assay, cell abnormalities associated to the malfunction/non-formation of mitotic spindle (aneugenic effect) and chromosomal bridges (clastogenic effect) were observed. The results indicate a cytogenotoxic activity of β-ecdysone. Therefore, the popular use of Pfaffia and others species containing β-ecdysone should be considered with caution.
Keywords: Pfaffia glomerata; Brazilian ginseng; Cytogenotoxicity; Rodent bone marrow micronucleus Assay; Allium cepa Assay; β-ecdysone